Clinical utility of self-expandable metal stents in the treatment of anastomotic obstruction secondary to recurrent gastric cancer - Lai, Haiyang; Wu, Ketong; Liu, Yang; Li, Dan; Peng, Tao; Wan, Yuan; Zhang, Bo (Frontiers in Oncology, 2025)
AimThe purpose of this study was to assess the efficacy and safety of self−expandable metal stents (SEMS) in treating anastomotic obstruction associated with recurrent gastric cancer.MethodsTen patients with anastomotic obstruction in recurrent gastric cancer were treated by SEMS implantation under fluoroscopic guidance. All patients presented with refractory nausea, vomiting and complete inability to tolerate oral intake before stent placement, requiring total parenteral nutrition (TPN). Clinical data were retrospectively analyzed the technical and clinical success rates, stent patency and complication rates.ResultsSEMS was successfully implanted in all patients, and clinical success rate was 100%. The operations were subtotal gastrectomy with Billroth-II reconstruction (n = 3), radical distal gastrectomy (n = 3), total gastrectomy with esophagojejunostomy (n = 3), and palliative gastrojejunostomy (n = 1). Three patients developed stent occlusion due to intrastent tumor ingrowth secondary to disease progression after initial anastomotic stent placement, and underwent secondary stent implantation with successful maintenance of patency postoperatively. One patient developed stent obstruction due to food impaction on postoperative day 10, which was managed endoscopically with successful restoration and maintenance of luminal patency. The mean stent patency was 78 d (range, 8–225 d). No serious complications, such as anastomotic leakage, stent migration and bleeding were observed in these patients.ConclusionsFluoroscopically-guided SEMS placement represents a technically safe and clinically effective intervention for managing anastomotic obstructions in recurrent gastric cancer. SEMS placement offers rapid symptom relief, shorter hospital stays, and improved quality of life compared to surgical alternatives in this patient population. Thus, based on its technical feasibility and clinical outcomes, this method warrants primary consideration in palliative treatment algorithms.